2021
DOI: 10.1007/jhep05(2021)059
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Regge theory at finite boost

Abstract: The Operator Product Expansion is a useful tool to represent correlation functions. In this note we extend Conformal Regge theory to provide an exact OPE representation of Lorenzian four-point correlators in conformal field theory, valid even away from Regge limit. The representation extends convergence of the OPE by rewriting it as a double integral over continuous spins and dimensions, and features a novel “Regge block”. We test the formula in the conformal fishnet theory, where exact results involving nontr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The extra phase comes from the additional Wick rotations. The final result matches the definition of the discontinuity in [42]. Note that z is continued an extra half circle in opposite directions for the first two lines in (4.4), so that with these definitions the relation to the dDisc in (2.14) remains valid.…”
Section: Ads Impact Parameter Spacesupporting
confidence: 66%
See 1 more Smart Citation
“…The extra phase comes from the additional Wick rotations. The final result matches the definition of the discontinuity in [42]. Note that z is continued an extra half circle in opposite directions for the first two lines in (4.4), so that with these definitions the relation to the dDisc in (2.14) remains valid.…”
Section: Ads Impact Parameter Spacesupporting
confidence: 66%
“…Next we have to analyze the discontinuities on the right hand side of the optical theorem (4.5). The discontinuity of the scalar s-channel block was recently computed in general without taking the Regge limit in [42] and we will review it here. The generalization to external spinning operators is done in section 4.4, after taking the Regge limit.…”
Section: S-channel Discontinuities In the Regge Limitmentioning
confidence: 99%
“…88 Another approach could be via alternative representations of the 4-point function having an extended region of analyticity, e.g. [92].…”
Section: Discussionmentioning
confidence: 99%
“…For this it might not be necessary to understand the Reggeon or more general light-ray operators, since the resummation procedure can be stopped at a point where the correlator is expressed as an integral of C(∆, ) over a region where LIF converges. See[92] for progress on these questions. Papers by this group of authors are characterized by the systematic use of momentum space in Lorentzian CFT.…”
mentioning
confidence: 99%
“…(1.1) With this assumption, all the operators in a given sector are lifted together. The main motivation to this analysis comes from recent works on conformal Regge theory and lightcone bootstrap [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], which showed that CFT operators organize in families, or Regge trajectories. Hence, a twist gap corresponds to imposing that the leading Regge trajectory lies above a certain line.…”
Section: Jhep05(2021)111mentioning
confidence: 99%